The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.jag.2006.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Determining iron content in Mediterranean soils in partly vegetated areas, using spectral reflectance and imaging spectroscopy

Abstract: The possibility of quantifying iron content in the topsoil of the slopes of the El Hacho Mountain complex in Southern Spain using imaging spectroscopy is investigated. Laboratory, field and airborne spectrometer (ROSIS) data are acquired, in combination with soil samples, which are analysed for dithionite extractable iron (Fed) content. Analysis of the properties of two iron related absorption features present in laboratory spectra demonstrates good relations, especially between the standard deviation (S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 21 publications
0
41
0
1
Order By: Relevance
“…A high variability of model performances was reported in several studies dealing with texture prediction by RS [80][81][82][83][84][85]. [84] or even better [86,87] in comparison to other studies. In conclusion, the analysis showed that the distribution of soil properties in eroded landscapes can be successfully predicted using the spectroscopic data.…”
Section: Prediction Of Soil Properties By Imaging Spectroscopymentioning
confidence: 98%
“…A high variability of model performances was reported in several studies dealing with texture prediction by RS [80][81][82][83][84][85]. [84] or even better [86,87] in comparison to other studies. In conclusion, the analysis showed that the distribution of soil properties in eroded landscapes can be successfully predicted using the spectroscopic data.…”
Section: Prediction Of Soil Properties By Imaging Spectroscopymentioning
confidence: 98%
“…Although it may not be as important for soil fertility as e.g., phosphorus, nitrogen and organic matter, its absence would be detrimental to plant growth. Iron is thus an indicator for soil fertility and the usability of an area for cultivation of crops [27]. A relative high spectral resolution is needed for mapping iron contents with reflectance data [26], and remote sensing is the only suitable tool for surveying large areas at a high temporal and spatial interval.…”
Section: Introductionmentioning
confidence: 99%
“…The use of hyperspectral techniques has also demonstrated the quantification, which is attractive for soil scientists due to the reduction in the need for time-and cost-intensive soil laboratory analyses and field campaigns [1]. Several studies have demonstrated that such soil characteristics can be quantified and predicted statistically via their spectral signatures in the commonly used/accessible VNIR-SWIR wavelength region [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%